Approximation Algorithms for Cell Planning in Heterogeneous Networks - Zhao, Wentao; Wang, Shaowei; Wang, Chonggang; Wu, Xiaobing (IEEE transactions on vehicular technology, 2017)
Small cells are introduced to cellular systems to enhance coverage and improve capacity. Densely deploying small cells can not only offload the traffic of macrocells but also provide an energyand cost-efficient way to meet the sharp increase in traffic demands in mobile networks. However, such a cell deployment paradigm also leads to heterogeneous network (HetNet) infrastructure and raises new challenges for cell planning. In this paper, we study the cell planning issue in the HetNet. Our optimization task is to select a subset of candidate sites to deploy macro or small cells to minimize the total cost of ownership (TCO) or the energy consumption of the cellular system while satisfying practical constraints. We introduce approximation algorithms to cope with two different cell-planning cases, which are both NP-hard. First, we discuss the macrocell-only case. Our proposed algorithm achieves an approximation ratio of O(log R) in this scenario, where R is the maximum achievable capacity of macrocells. Then, we introduce an O(log R̃)-approximation algorithm to the smallcell scenario, where R̃ is the maximum achievable capacity of a macrocell with small cells overlaid on it. Numerical results indicate that the HetNet can significantly reduce the TCO and the energy consumption of the cellular system.